2012
DOI: 10.1590/s1980-65232012000200016
|View full text |Cite
|
Sign up to set email alerts
|

Orthokeratinized odontogenic cyst: a report of two cases in the mandible

Abstract: Purpose: To describe the behavior clinical and pathological features of two cases of odontogenic cyst orthokeratinized. Case description: In case 1, a 17-year-old woman presented hard and painless swelling in the left posterior mandible. Radiographically, a radiolucent area with a radiopaque was observed. A clinical diagnosis of ameloblastoma or odontogenic keratocystic tumor was established. The histopathological examination revealed an orthokeratinized odontogenic cyst. In case 2, a 23-year-old woman present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
(46 reference statements)
2
7
0
Order By: Relevance
“…There is a male predominance and the majority of cases were associated with unerupted teeth, which is in agreement with our findings and previous studies [7]. All the cases were treated conservatively and two reported no recurrences [14,17].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There is a male predominance and the majority of cases were associated with unerupted teeth, which is in agreement with our findings and previous studies [7]. All the cases were treated conservatively and two reported no recurrences [14,17].…”
Section: Discussionsupporting
confidence: 93%
“…At the present time however, there is no convincing evidence to link multiple OOCs to NBCCS or Gardner Syndrome. Table 1 summarises four previous reports of bilateral or multiple OOCs reported in the literature [14,[16][17][18]. Similar to the cases reported here, the patients were of a relatively young age, with three of the four reports involving an individual in their third decade.…”
Section: Discussionsupporting
confidence: 66%
“…Although the histogenesis of OOC is unclear, it is suggested that (a) OOCs could be dentigerous cysts with orthokeratinization as reduced enamel epithelium after tooth formation has the capacity to keratinize under appropriate stimuli, (b) OOCs may represent central dermoid/epidermoid cysts due to similar histological features, (c) OOCs may arise from oral epithelium under the influence of dental papilla or only the oral epithelium and (d) sequestration of the stomodeal ectoderm into the developing jaw during embryogenesis may be a source of origin of OOC. [ 2 5 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Multilocular and bilateral cases also have been reported. [ 2 8 ] Most of the OOCs show striking feature of buccolingual expansion. [ 4 10 ] This helps to differentiate it from OKC which shows anteroposterior growth pattern without causing obvious bone expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical findings in OOC confirm their non-aggressive behavior when compared to KCOT. [ 7 ] An immunohistochemical analysis of present case was done for proliferative activity by Ki-67 [ Figure 7 ] and anti-apoptotic activity by bcl-2 [ Figure 8 ]. Ki 67 was positive in few cells of basal layer and bcl-2 expression was negative.…”
Section: Discussionmentioning
confidence: 99%